Smart Caching for Web Browsers - Zhang, Kaimin; Wang, Lu; Pan, Aimin; Zhu, Bin Benjamin (WWW 2010, 2010)
In modern Web applications, style formatting and layout calculation often account for a substantial amount of local Web page processing time. In this paper1, we present two novel caching schemes, the smart style caching and the layout caching, for Web browsers. They cache stable style data and layout data for DOM (Document Object Model) elements, and apply directly without re-calculation when the same data is subsequently processed, possibly across different visits of a Web page. Redundant computations in both style formatting and layout calculation could be eliminated, resulting in more efficient local Web page processing. The proposed caching schemes are still applicable and effective even there are changes in the DOM structure or style rules of a Web page. The experiments on the homepages of the Top 25 Web sites show that on average, in a subsequent visit of the same Web page, the smart style caching could reduce the style formatting time by about 64%, and the combination of both caching schemes could reduce the layout calculation time by about 61%, with about 46% overall performance improvement on the local Web page processing time. For the overall performance when networking, Web servers, and local Web page processing were all included, our caching schemes could improve up to 56% when browsing these Web sites on a desktop PC and up to 60% when browsing on a netbook.